The degree of skin involvement identifies distinct lung disease outcomes and survival in systemic sclerosis. Issue 6 (20th April 2013) - Cottrell, Tricia R; Wise, Robert A; Wigley, Fredrick M; Boin, Francesco
Abstract : Objective: To determine whether the pattern of skin involvement can predict clinical features, risk of restrictive lung disease (RLD) and survival in a large scleroderma (SSc) cohort. Methods: Demographic and clinical data collected over 30 years from 2205 patients with SSc were retrospectively analysed after subdividing subjects into four subtypes based on pattern of skin fibrosis: type 0 (no skin involvement), type 1 (limited to metacarpophalangeal joints), type 2 (distal to elbows/knees) and type 3 (proximal to elbows/knees). Clinical features associated with skin subsets were identified by regression analyses. Kaplan–Meier and Cox proportional hazards models were used to compare time to RLD and survival across subtypes. Results: The presence and severity of RLD were positively associated with skin subtype (p<0.001). RLD prevalence incrementally ranged from 51.9% in type 0 to 76.7% in type 3 (p<0.001). Type 2 SSc exhibited a distinct phenotype with intermediate risk for RLD relative to type 1 (higher, p<0.001) and type 3 (lower, p<0.001) and a unique autoantibody profile, with a prevalence of anticentromere antibodies lower than type 1 (28.9% vs 44.1%, p=0.001) and of anti-topoisomerase I antibodies similar to type 3 (32.8% vs 28.7%, p=0.38). These autoantibodies were also found to be significant negative (OR=0.33, p<0.001) and positive (OR=1.6, p=0.01) predictors of RLD risk, respectively. Mortality was also intermediate in type 2 patients relative to type 3 (p=0.0003) and type 1 (p=0.066). Conclusions: These data suggest that the current classification subdividing SSc into limited and diffuse cutaneous subtypes misclassifies an intermediate group of patients exhibiting unique autoantibody profile, disease course and clinical outcomes.